Influence of operating parameters on the rejection of zinc ions from aqueous solution by a nanofiltration polyamide membrane - Wallace, Edwin; Cuhorka, Jiří; Mikulášek, Petr (Slovenská spoločnosť chemického inžinierstva, 2017)
This work focuses on the potential use of a commercial thin-film composite polyamide nanofiltration membranes for removal of extremely polluting and toxic Zn (II) ions from wastewater. The experiments have been performed for aqueous solutions containing zinc over a wide range of concentration in batch mode with total recycle of permeate and retentate. The influence of operating conditions such as applied pressure, feed concentration, cross-flow velocity and pH was examined. Only at lower fluxes, rejection of zinc ions increases with increasing feed concentration in concentration range tested. A plateau of the observed rejection has been reached at pressure higher than 20 bar. The maximum rejection of zinc ions was 99.3% without regard to the concentration range (50–200 mg Zn/L). For evaluation of cross-flow velocity, the film model has been used. In addition, the real retention was almost independent on the feed flow rate. From the results obtained, AFC 30 membrane can be highly recommended for removing of heavy metals such as zinc from wastewater.
Vliv provozních parametrů na rejekci zinku polyamidovou nanofiltrační membránou
Keywords: Zinc ions; Nanofiltration; Polyamide membrane; Rejection; Ionty zinku; Nanofiltrace; Polyamidová membrána; Rejekce